2017
DOI: 10.3892/etm.2017.5648
|View full text |Cite
|
Sign up to set email alerts
|

Pine needle oil induces G2/M arrest of HepG2 cells by activating the ATM pathway

Abstract: Over the last two decades, inducing DNA damage of cancer cells by natural medicines has become a research hotspot in the field of cancer treatment. Although various natural medicines have anticancer effects, very few studies have been conducted to explore the anti-cancer effect of pine needle oil. In the present study, the role of pine needle oil in inducing G2/M arrest in HepG2 cells was investigated. The data revealed that pine needle oil could induce DNA damage in a dose-dependent manner. In the pine needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The G2/M checkpoint ensures that cells undergo all the necessary changes during the S and G2 phases and are ready for division (Hyun, Becam, Yanicostas, & Bohmann, ; Stark & Taylor, ). Therefore, inducing G2/M arrest is an effective strategy to control the proliferation of cancer cells (Qiu et al, ). Our finding that knockdown of CtIP facilitates cell proliferation after Eto treatment suggests that CtIP may be involved in the regulation of Eto‐induced G2/M arrest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The G2/M checkpoint ensures that cells undergo all the necessary changes during the S and G2 phases and are ready for division (Hyun, Becam, Yanicostas, & Bohmann, ; Stark & Taylor, ). Therefore, inducing G2/M arrest is an effective strategy to control the proliferation of cancer cells (Qiu et al, ). Our finding that knockdown of CtIP facilitates cell proliferation after Eto treatment suggests that CtIP may be involved in the regulation of Eto‐induced G2/M arrest.…”
Section: Resultsmentioning
confidence: 99%
“…G1/S and G2/M are two major cell-cycle checkpoints that ensure proper cell-cycle progression. G2/M arrest is caused by DNA damage and is also regulated by DNA damage repairrelated proteins, such as ataxia-telangiectasia mutated (ATM) (Hua et al, 2013;Qiu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated the apoptotic effects of TW oil on HepG2 liver cancer cell lines 22 . Further studies have shown that TW oil facilitates cell cycle arrest in HepG2 cells 23 . Chrysin is a biologically active dietary flavonoid in many plants and has been known to be the most active bioactive component in TW extract and has been known to induce apoptosis and suppress autophagic clearance 16,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…22 Further studies have shown that TW oil facilitates cell cycle arrest in HepG2 cells. 23 Chrysin is a biologically active dietary flavonoid in many plants and has been known to be the most active bioactive component in TW extract and has been known to F I G U R E 4 Effect of P. morrisonicola Hayata extract (PE) on apoptosis: (A) Flow cytometry analysis of HA22T cells show increase in apoptotic cell numbers upon PE treatment. PE showed better effect than chrysin.…”
Section: Pe Downregulates Autophagic Proteins That Were Correlated Wi...mentioning
confidence: 99%
“…23,24 Pine needle oil treatment arrested the Hepg2 cycle cell and inhibited the proliferation of liver cancer cell line. 25 Other parts of the tree possess remarkable antioxidant, anti-inflammatory and antimicrobial activities. 26,27 Plant-derived products with a wide range of phytochemicals and phenolic compounds have considerable as an antioxidant, antiradical, antiinflammatory and anticarcinogenic activities.…”
Section: Discussionmentioning
confidence: 99%